Coagulation mechanism of polyaluminum manganese chloride in alkaline conditions: Role of manganese in changing hydrolysates and coordination structure - Yanli Kong; Pengjun Zhang; Shunliang Hu; Yunlong Xie; Zhonglin Chen; Jiangya Ma (Journal of Environmental Sciences, 2026)

Nanostructured Fe2(MoO4)3 cathodes: Enhancing ion and electron kinetics for high-rate and low-temperature sodium-ion batteries - Ting Zhao; Hang Liu; Gacao Dou; Dongting Zhang; Junqiang Qiao; Juan Yang; Pengjun Ma; Cuiying Lu; Hongxia Li; Hongruo Ma; Kunjie Wang; Bingjun Yang (Chemical Engineering Journal, 2026)

Enhanced defluoridation using covalently bonded organosilicon-bimetallic composite coagulants: Al-Mg and Al-Fe driven divergence in hydrolysis speciation and active site substitution pathways - Yahua Zhou; Zhiyu Li; Pengjun Zhang; Yanli Kong; Jiangya Ma (Water Research, 2026)

Discovering Changes in the Global Liquefied Natural Gas Marine Supply Network During the Russian-Ukrainian Crisis with Big Data - Renrong Xiao; Pengjun Zhao; Mengzhu Zhang; Tingting Kang; Tianyu Ma (Chinese Geographical Science, 2025)

Liquefied natural gas trade network changes and its mechanism in the context of the Russia–Ukraine conflict - Renrong Xiao; Pengjun Zhao; Kangzheng Huang; Tianyu Ma; Zhangyuan He; Caixia Zhang; Di Lyu (Journal of Transport Geography, 2025)

Coagulation performance and mechanism of different novel covalently bonded organic silicon-aluminum/iron composite coagulant for As(V) removal from water: The role of hydrolysate species and the effect of coexisting microplastics - Yanli Kong; Yahua Zhou; Pengjun Zhang; Yong Nie; Jiangya Ma (Journal of Hazardous Materials, 2024)

Photothermal conversion-enhanced thermoelectric generators combined with supercapacitors: An efficacious approach to integrated power generation and storage - Pengjun Ma; Yan Wang; Xu Zhang; Bingjun Yang; Junwei Lang; Juan Yang; Zhonghao Wang; Abdukader Abdukayumb; Guangzhi Hu (Chemical Engineering Journal, 2024)

Structure and resilience changes of global liquefied natural gas shipping network during the Russia–Ukraine conflict - Renrong Xiao; Ting Xiao; Pengjun Zhao; Mengzhu Zhang; Tianyu Ma; Shike Qiu (Ocean & Coastal Management, 2024)

Effects of Preparedness on Successful Emergency Response to Ship Accident Pollution Using a Bayesian Network - Yini Zhu; Wenqing Ma; Hongxiang Feng; Guiyun Liu; Pengjun Zheng (Journal of Marine Science and Engineering, 2022)
With the rapid development of international trade and the fast growth of port freight volumes, the risk of ship pollution in marine areas has significantly increased. Frequent ship pollution accidents seriously endanger marine ecosystems and are extremely unfavorable to economic development and marine environmental protection. In this study, we investigate the results of emergency responses after ship pollution accidents and analyze the factors affecting a successful emergency response. A Bayesian network model of the emergency response results of ship pollution is established, and the emergency response results of ship pollution accidents in the example of Zhoushan Port are analyzed. Based on the analysis, suggestions for strengthening the emergency preparedness of Zhoushan Port are proposed. We believe that the results of this are beneficial for improving ship pollution risk management and decision making, and that they have practical significance for marine environmental protection.